STracking: a free and open-source python library for particle tracking and analysis - Prigent, Sylvain; Valades-Cruz, Cesar Augusto; Leconte, Ludovic; Salamero, Jean; Kervrann, Charles (bioRxiv, 2022)
Analysis of intra and extra cellular dynamic like vesicles transport involves particle tracking algorithms. Designing a particle tracking pipeline is a routine but tedious task. Therefore, particle dynamics analysis is often performed by combining several pieces of software (filtering, detection, tracking...) requiring a lot of manual operations, and therefore leading to poorly reproducible results. A good synergy between particle detector with a tracker is of paramount importance. In addition, a user-friendly interface to control the quality of estimated trajectories is necessary. To address these issues, we developed STracking a python library that allows to combine algorithms into standardized particle tracking pipelines. Competing Interest Statement The authors have declared no competing interest.